Treatment of Lower Extremity Fractures in Chronic Spinal Cord Injury: A Systematic Review of the Literature. Issue 5 (25th August 2020) - Huang, Donna; Weaver, Frances; Obremskey, William T.; Ahn, Jaimo; Peterson, Kimberly; Anderson, Johanna; Veazie, Stephanie; Carbone, Laura D.
Abstract : Objective: To review the literature regarding outcomes of surgical and nonsurgical management of lower extremity (LE) fractures in chronic spinal cord injury (SCI). Type: Systematic review. Literature Survey: Medline (PubMed), Embase, Cochrane Database of Systemic Reviews, Cochrane Central, Cumulative Index to Nursing and Allied Health Literature, ClinicalTrials.gov, International Clinical Trials Registry Platform, and International Standard Randomized Controlled Trials were searched from January 1, 1966, to March 1, 2019. Methodology: Search was restricted to English language and adults (age ≥ 18 yr). Titles and abstracts were reviewed for relevance to study topics for inclusion. Case reports, reviews, non‐SCI population studies, and studies examining fractures at the time of acute SCI were excluded. References of included articles from the original search and task force and external submissions yielded two additional articles that were included in the review after voting by task force members. Data extraction was performed by four task force members using a data extraction form, glossary, and instructions created in Microsoft Excel. Quality assessment was performed by three methodologists using prespecified criteria. Synthesis: Twenty‐three articles were included. Use of surgery to treat LE fractures in chronic SCI has increased, though nonoperative management was still more frequently reported. Regardless of type of management, amputations, nonunion/malunion, and pressure injuries were among the most commonly reported complications. Functional and quality of life outcomes were less frequently reported. Conclusions: There is insufficient evidence to support operative versus nonoperative management as best practice for management of LE fracture of SCI. Existing literature was limited by small sample sizes, lack of randomization or matched study designs, significant heterogeneity in populations and treatment strategies studied, and variability in defining and reporting outcomes of interest. The field would benefit from future research to address study design issues and standardization of outcome reporting to facilitate comparison of outcomes of operative versus nonoperative management.